2022
DOI: 10.3390/ijms23147730
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glucose Ameliorates Impaired Intestinal Development and Immune Homeostasis Disorders Induced by Chronic Cold Stress in Pig Model

Abstract: Endotherms are easily challenged by chronic cold stress. In this study, the development and injury of the small intestine in the Min pig model and Yorkshire pig model under chronic cold stress, and the molecular mechanisms by which glucose supplementation reduces small intestinal mucosal damage were investigated. The results showed that morphological structure lesions of the jejunal mucosa and ileal mucosa were visible in Yorkshire pigs under chronic cold stress. Meanwhile, the Occludin mRNA and protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(62 reference statements)
0
9
1
Order By: Relevance
“…54,55 Our previous study showed that prolonged cold stimulation induces inflammation by activating the TLR4/NLRP3 signaling pathway in the small intestinal mucosa and lungs. 18,19 In the present study, there was no effect on the protein expression of MyD88 even though its mRNA expression was enhanced during prolonged cold stimulation. Nevertheless, the protein levels of NLRP3 and mature-Il-1β were promoted.…”
Section: Papercontrasting
confidence: 61%
See 3 more Smart Citations
“…54,55 Our previous study showed that prolonged cold stimulation induces inflammation by activating the TLR4/NLRP3 signaling pathway in the small intestinal mucosa and lungs. 18,19 In the present study, there was no effect on the protein expression of MyD88 even though its mRNA expression was enhanced during prolonged cold stimulation. Nevertheless, the protein levels of NLRP3 and mature-Il-1β were promoted.…”
Section: Papercontrasting
confidence: 61%
“…18 TLR4 induces nuclear factor-κB (NF-κB) activation and nuclear translocation via MyD88, which leads to the triggering of pro-IL-1β and NLRP3 expression. 18 NLRP3 binds to apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), and links to caspase-1 through the CARD structural domain within ASC, as well as forming NLRP3 inflflammasomes. 54 NLRP3 inflammatory vesicles shear pro-IL-1β and pro-IL-18 into their respective mature forms, and promote the formation of the gasdermin D (GSDMD) N-terminal domain, which oligomerizes and moves to the cell membrane to form pores, ultimately resulting in the release of intracellular inflammatory factors and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the trypsin activity in jejunal mucosa had a trend toward inhibition in the CSY group, suggesting that protein digestion ability was weakened. Studies have shown that chronic cold stress modulates intestinal inflammatory cell infiltration, intestinal development and mucosal barrier function ( Liu et al., 2019 ; Sun et al., 2022 ). Thus, chronic cold exposure may dilute the ability for the small intestine to digest crude protein by inducing damage to the small intestine.…”
Section: Discussionmentioning
confidence: 99%